Influence of the Size and the Angle of Branches Connected to the Main Horizontal Pipe on the Onset of Gas Entrainment - Gao, Jinchen; Yue, Yanwei; Meng, Zhaoming; Li, Xiaoyu; Shen, Geyu (Frontiers in Energy Research, 2020)
The influence of the size and the angle of the branch on the onset of gas entrainment is explored in the present study. Since previous studies were performed on small-sized branches and the angles of the branches were specific (0° or −90°), it is difficult to apply them to arbitrary-angled branches. So we conducted a series of experiments in a different direction of −30°, −45°, −60°, and −90° angles with the main pipe of 80-mm diameter and a branch of 31-mm diameter (T-tube). A new correlation is developed and can predict the most experimental data well within the error range of ±20%. And the new correlation can predict the onset of gas entrainment at arbitrary-angled branch and is not constrained by the angle of branches; that is, it has good versatility. We also gained some meaningful conclusions by analyzing experimental data and the entrainment phenomenon: gas is entrained by a vortex flow, and the size of the branch and the angle of the branch have little effect on the form of entrainment at a given hb/d. The critical Froude number (FrL) gradually increases as the angle of the branch changes from −90° to −30°. When this is compared with previous models, it can be found that the correlation of the onset of gas entrainment based on small-sized branches is not suitable for large-scale branches. But we have defined a new critical liquid level (hb*) to successfully expand the scope of application of the correlation.